Integrasi Nilai-Nilai Moderasi Beragama Dalam Kurikulum Pendidikan Islam di MA Alkhairaat Kota Gorontalo: Kajian Filosofis Dan Pedagogis - Wahidah, Nor Rochmatul; Kasidi (Moderatio: Jurnal Moderasi Beragama, 2024)
Islamic education based on religious moderation is one of the important strategies in building the character of the young generation who are tolerant, inclusive, and balanced in carrying out religious teachings. This article aims to analyze the integration of religious moderation values in the Islamic education curriculum under Madrasah Aliyah Alkhairaat Gorontalo City, using qualitative research methods. Philosophical and pedagogical approaches are used to examine the concept of religious moderation (wasathiyah) and its implementation in the learning process. This study collected data through in-depth interviews, document analysis, and literature studies. The results of the study show that the values of religious moderation, such as tolerance, justice, balance, and interfaith dialogue, have been integrated into the Islamic education curriculum through a values-based curriculum approach, inclusive learning methods, and strengthening teacher capacity. This integration has a positive impact on preventing radicalism and strengthening a balanced religious identity. Thus, Islamic education based on religious moderation can be an effective fortress in forming a harmonious society and preventing the emergence of extremism among students.